Correlates gender traits and mindset on the choice of physics subject at high school in Kenya - Eunice Ruraa Mugendi; Ciriaka Gitonga; Peter Rugano; Zachary Njagi Ndwiga (Institute of Advanced Engineering and Science, 2024)
Higher education and training in science, technology, engineering, and mathematics (STEM) are important for the industrial growth and development of any nation. Physics subject provides the basics for training in many STEM areas. However, failure to pursue physics to the end of high school denies learners opportunities in STEM courses. This research employed a correlational design and survey method to examine the relationship of gender traits (GT) and mindset (MS) with learners’ intention to choose physics among 378 high school students randomly sampled. The study adopted the gender traits test and mindset questionnaires. The Chi-square test for the relationship of GT and MS with the intention to choose a physics subject yielded p>0.05. These results revealed that no student is deprived of an opportunity to pursue physics to higher levels on account of their GT or MS. Thus, attempts to increase the number of learners who can potentially pursue STEM courses by studying physics in high school should focus on other known factors other than GT and MS.